Pengaruh Aksesibilitas dan Harga Terhadap Minat Kunjungan Ulang Wisatawan ke Daya Tarik Wisata (DTW) di Kecamatan Kintamani - Ni Kadek Suciati; I Putu Arya Dharmayasa (Jurnal Pendidikan Ekonomi Undiksha, 2026)
The study aims to determine (1) The influence of Accessibility on Tourists’ Intention to Revisit Tourist Attractions in Kintamani District, (2) The influence of Price on Tourists’ Intention to Revisit Tourist Attractions in Kintamani District, (3) The influence of Accessibility and Price on Tourists’ Intention to Revisit Tourist Attractions in Kintamani District. The population of this study consists of all tourists in Kintamani District at least once, both local and international tourists. The sampling technique used in this study is the non-probability sampling technique, with a sample size of 119 tourists. The data collection method used is a questionnaire and the data is analyzed using multiple linear regression analysis. The results of the date processing show that (1) there is a positive and significant influence of accessibility on Tourists’ Intention to Revisit, (2) there is positive and significant influence of Price on Tourists, (3) there is a positive and significant influence of Acessibility and Price on Tourists’ Interest in Revisiting.